Distribution Network Reconfiguration for Loss Reduction Methodology: A Review - Telugu Sreedhar, Nemmani Venkata Ramana (International Journal of Control and Automation, 2020)
A Distribution System Operator (DSO) who operates and develops distribution networks to deliver quality and reliable power to consumers at an affordable price with the support of system optimization. Power losses are indicative of the cost-effective operation and quality of the DSO’s activities. DSO has a distribution system comprising network, demand, generation and other flexible distributed energy resources (DER). Reduction of power loss is one of the most important business objectives of the DSO. Distribution Network Reconfiguration (DNR) or Feeder Reconfiguration (FR) is the most efficient methodology adapted by DSOs for loss reduction. DNR is a complex combinatorial optimization process aimed at finding a radial operating structure that minimizes the system power loss while satisfying operating constraints. This paper gives the brief review from the literature on DNR methodology with objective function, methods of optimization, features of optimizations, test system and contribution with results.